CREDIT PORTFOLIO OF A COMMERCIAL BANK: THE ESSENCE AND FEATURES OF THE OPTIMAL STRUCTURE FORMING - Король, Світлана; Смицнюк, Орест (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article examines scientific approaches to understanding the essence of the credit portfolio of a commercial bank. His author’s vision is proposed, which envisages a division in the plane of a narrow and a broad vision of essential characteristics. In a broad sense, the credit portfolio of a commercial bank is proposed to mean a set of tools with which the bank implements its credit policy and gains competitive advantages in the credit market. In a narrow sense, the loan portfolio is a set of loans that the bank provides to its customers to obtain interest income. With the help of statistical data, the commercial bank JSC "Ukreximbank" credit portfolio was analyzed for the period under study. It was established that credit investments occupy a significant part in the structure of assets of a commercial bank. Over the entire period of the study, there was a clear tendency to decrease the volume of loans granted by Ukreximbank, which is a negative phenomenon, since the decrease in the volume of lending entails a reduction in the bank’s profitability. This is due to the crisis in the country and the world - political and currency instability, which led to a decrease in the demand for credit products among legal entities. The main problems of the loan portfolio of JSC "Ukreximbank" were identified. An analytical assessment of the credit portfolio of a commercial bank made it possible to establish a strong relationship between the size of non-overdue and non-impaired loans and the bank’s interest income. The conducted studies proved that a qualitatively formed credit portfolio, i.e., the predominance of the share of non-overdue and unvalued debt in it, has a significant impact on the profitability of banking institutions. Particular attention was focused on the analysis of problem loans and the main directions for improving the quality of the loan portfolio were proposed. Strategies are also highlighted by which problem loans can be resolved in modern conditions, namely: leaving them on the balance sheet, selling them to a third party or getting rid of them by writing them off the balance sheet and stopping debt collection measures.